Hubungan Filsafat dengan Aspek-Aspek Pendidikan - Gandi, Agus; Fadjarani, Siti (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2025)
Abstract. The connection between philosophy and education is deeply intertwined, requiring a study of the relationship and its potential impact. Philosophy offers the theoretical foundation for educational practices and beliefs. This article uses a literature review methodology, drawing from both international and national sources via QuillBot, to explore how philosophical thinking can enhance educational practices. By integrating philosophical concepts into educational settings, educators can empower students to think critically, question assumptions, and make informed decisions. This not only enhances students' academic capabilities but also helps them develop a strong moral compass and social responsibility. Further research opportunities on this topic include examining the long-term effects on students' critical thinking skills, exploring teaching methods that effectively incorporate philosophical concepts into curricula, and investigating the impact of philosophical education on students' personal values and ethical decision-making. Ultimately, embedding philosophy into education has the potential to foster well-rounded, ethically-conscious individuals capable of making thoughtful and responsible choices in a complex world.